2012
DOI: 10.1152/japplphysiol.00605.2011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic and pro-survival effects of exercise training on hypertensive hearts

Abstract: Exercise training prevented hypertension-enhanced cardiac Fas-dependent and mitochondria-dependent apoptotic pathways and enhanced cardiac pro-survival pathway in rat models. Our findings demonstrate new therapeutic effects of exercise training on hypertensive hearts for preventing apoptosis and enhancing survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 29 publications
8
95
0
5
Order By: Relevance
“…Furthermore, we also found that appropriate exercise training can enhance the PI3K-Akt pathway (Lee et al 2008;Huang et al 2012;Cheng et al 2013;Lee et al 2013). In FOXO3, the three sites phosphorylated by Akt are Thr32, Ser253, and Ser315.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, we also found that appropriate exercise training can enhance the PI3K-Akt pathway (Lee et al 2008;Huang et al 2012;Cheng et al 2013;Lee et al 2013). In FOXO3, the three sites phosphorylated by Akt are Thr32, Ser253, and Ser315.…”
Section: Introductionmentioning
confidence: 60%
“…These data suggest that exercise training, resveratrol treatment, and exercise training combined with resveratrol treatment can all be cardioprotective. Our previous report revealed an antihypertrophic effect in rat hearts from exercise training (Lee et al 2008;Huang et al 2012;Cheng et al 2013;Lee et al 2013). Indeed, the collagen accumulation in the exercise training rat hearts was not as severe as that in the control group (Figs.…”
Section: Discussionmentioning
confidence: 79%
“…This can be reduced by exercise training. Our previous reports revealed an anti-hypertrophic effect in rat hearts through exercise training (Chang et al 2013;Lee et al 2013;Lee et al 2008;Huang et al 2012). This aging model expression after stimulation is weakened with increasing age.…”
Section: Discussionmentioning
confidence: 95%
“…The apoptotic pathway exhibits increased levels with a reduced survival pathway in these situations. Exercise training and eating purple sweet potato yogurt can help to prevent heart failure and apoptosis Kuo et al 2005;Lin et al 2013;van Tol et al 2006;Huang et al 2012). Spontaneously hypertensive rats (SHR) of advanced age exhibit depressed myocardial contractile function and ventricular fibrosis, and as a result, stable compensatory hypertrophy progresses to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential candidates have been previously evaluated in the myocardium, as follows: antioxidant defense (Pinho et al, 2012); increased angiogenesis (Leosco et al, 2012); favorable inflammatory status (Beavers, Brinkley, & Nicklas, 2010). There is a growing body of evidence showing that AET is associated with an beneficial modulation of programmed cell death (apoptosis) of the cardiomyocytes (Huang et al, 2012;Siu, Bryner, Martyn, & Alway, 2004). The apoptosis is a type of cellular death that allows the elimination of nonfunctional, abnormal, or damaged as well as harmful cells (Cohen, 1997;Thompson, 1995).…”
Section: Introductionmentioning
confidence: 99%